Methane oxidation over Pt, Pt:Pd, and Pd based catalysts: Effects of pre‐treatment. (17th June 2015) - Abbasi, Reza; Huang, Guangyu; Istratescu, Georgeta M.; Wu, Long; Hayes, Robert E.
<x xml:space="preserve">Abstract</x> This paper presents a comparison of the activity for methane oxidation of selected commercial platinum, palladium, and platinum‐palladium supported catalysts. Precious metal loadings are typical of those found in the catalytic converters for lean‐burn natural gas engines. Experiments are presented for de‐greened as well as hydrothermally aged catalysts, both in the presence and the absence of water. For the platinum catalyst, fraction conversion of methane is shown to be independent of methane concentration, while for the palladium‐containing catalysts a dependence of conversion on methane partial pressure is observed. For catalysts containing palladium, reduction in hydrogen gives an increase in methane conversion activity, although the increase is subsequently lost in the oxidizing atmosphere. Hydrothermal aging of the platinum catalyst causes a relatively large and permanent loss in methane oxidation activity, while the palladium‐based catalysts showed more resistance to deactivation. Adding a small amount of palladium to the platinum catalyst provides an overall improvement in performance.